Hepatite autoimune e colangite esclerosante primária em crianças e adolescentes: avaliação dos fatores imunofenotípicos - Priscila Menezes Ferri (2016)
Primary sclerosing cholangitis (PSC) is a rare cholestatic liver disease characterized by chronic inflammation of the biliary tree resulting in liver fibrosis that predominates on male with less than 40 years. The diagnostic of PSC is based on clinical, laboratory and image findings. Differences in clinical and laboratory findings were observed in young patients include higher incidence of overlap syndrome, higher serum levels of aminotransferases and gama-glutamyl transferase and lower incidence of serious complications such as cholangiocarcinoma. In a spite of the detection of several HLA variants as associated factors in large multicentre cohorts of adult patients, the exact role and pathways of these susceptibility genes remain to be determined in pediatric population. Besides, the literature supports a role for an altered immune response to pathogens in the pathogenesis of PSC. This phenomenon contributes to abnormal immune system activation and perpetuation of an inflammatory process. Since these findings have been insufficient to characterize and determine the outcome, we propose a review of literature commenting how the immune and genetic factors could help on diagnosis and treatment decisions in child population.